High‐Temperature HCl Evolutions From Mixtures of Perchlorates and Chlorides With Water‐Bearing Phases: Implications for the SAM Instrument in Gale Crater, Mars. Issue 2 (11th February 2020) - Clark, J. V.; Sutter, B.; McAdam, A. C.; Rampe, E. B.; Archer, P. D.; Ming, D. W.; Navarro‐Gonzalez, R.; Mahaffy, P.; Lapen, T. J.
Abstract: Evolved hydrogen chloride (HCl) detected by the Sample Analysis at Mars (SAM) instrument's evolved gas analysis (EGA) mode on board the Mars Science Laboratory Curiosity rover has been attributed to oxychlorines (i.e., perchlorates and chlorates) or chlorides in Gale crater samples. Previous laboratory EGA studies of oxychlorines have been unable to reproduce the high‐temperature (>600 °C) HCl evolutions observed in most Gale crater samples. The objective of this work was to reproduce these high‐temperature HCl releases from laboratory mixtures of perchlorates and chlorides with phases that evolve water upon heating. Magnesium and sodium perchlorate and chloride were mixed with saponite, nontronite, and a basaltic glass and analyzed in a laboratory thermal evolved gas analyzer configured to operate similarly to the SAM instrument. Na perchlorate and chloride evolved HCl only when mixed with all three water‐producing phases. Mg perchlorate and chloride evolved a mid ‐temperature HCl release (~450–550 °C) and evolved an additional high‐temperature HCl release (~810–820 °C) when mixed with saponite. This work demonstrated that chlorides, either originally present or from perchlorate decomposition, evolved high‐temperature HCl when reacting with water from water‐producing phases. The HCl release temperature was dependent on the mixture's mineralogy and chemical composition. HCl releases detected by SAM were consistent with oxychlorines and/or chlorides in the presence of water‐producing phases. Additionally, this work provided constraints on the presence of oxychlorines or chlorides and their cation types, which has implications for past aqueous and diagenetic processes, the potential for past life, and detection of organics by EGA. Plain Language Summary: The detection of gaseous hydrogen chloride (HCl) on Mars can indicate the presence of oxychlorines (ClO4 or ClO3 ) or chlorides, which have implications for past physical and chemical changes in the rock, the detection of organics, and the potential that microbial life existed in the past. The Sample Analysis at Mars (SAM) instrument on Curiosity has detected gaseous HCl during the heating of solid rock and soil samples, but its origin is not well understood. Perchlorates and chlorides were mixed with materials that release gaseous H2 O upon heating and analyzed in a SAM‐analog instrument. Results indicated that chlorides and/or perchlorates reacting with water caused the HCl releases detected by SAM. The presence of perchlorates is significant because they could have served as fuel for past microbial life but can also hinder the detection of organic material. Perchlorates and chlorides also provide information on the geologic history of the area. Key Points: High‐temperature (>600 °C) HCl evolutions in SAM data were caused by oxychlorine phases or chlorides reacting with water Oxychlorine phases mixed with water‐producing phases evolved oxygen and hydrogen chloride Chlorides mixed with water‐producing phases evolved hydrogen chloride but did not evolve oxygen